A Statistical Study to Investigate the Efficiency of Steel and Polypropylene Fiber in Enhancing the Durability Properties of Concrete Composites - Singh, Niraj Kumar; Rai, Baboo (Civil Engineering Journal, 2018)
Concrete deterioration is associated with factors like surface abrasion and transport of water through capillary action in the concrete matrix. These factors may catalyze other forms of deformation such as cracking and corrosion of reinforcing steel. This paper presents an experimental evaluation to compare the effectiveness of steel and polypropylene fiber in enhancing the mechanical and durability properties, in terms of impact, sorptivity, and abrasion. In the present study, abrasion resistance is strongly related to flexural strength as high correlation coefficient existed as compared to that of compressive strength and split tensile strength. Sorptivity test results demonstrated a substantial decrease in capillary porosity when PPF is used in concrete. Â The average initial sorptivity versus fiber volume fraction represents a linear relationship with high R2 value. Positive correlations were also detected between abrasion and initial sorptivity of ordinary Portland cement concrete composite with polypropylene fiber.Â